Monitoring, Evaluating and Furthering the Commercial Usage of Tourism and Hospitality Industry Research Projects in 2017 - Kittinorarat, Jakkrapan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
Tourism and Hospitality Industry Research Projects funded by the National Research Council of Thailand in coordination with the Thailand Research Fund in the year 2017 mostly aim to tourism development in the northern region, especially in the tourism development zone "Lanna Civilization" by studying cultural and historical tourism Most of the findings are beneficial as the suggestions to be used to formulate strategies, policy suggestions, development guidelines, leading to important body of knowledge to enhance the competitiveness of Thai tourism industry. The analytic results also indicated that Tourism and Hospitality Industry Research Projects funded by the National Research Council of Thailand in coordination with the Thailand Research Fund in the year 2017 have been implemented in accordance with Strategies 1,3, and 6 of the 9th National Research Strategy (2017-2021), and Strategy 3 of Thai Tourism Strategy in 2015 – 2017. In addition, the said projects also have been implemented to be in line with the 2nd National Tourism Development Plan (2017 - 2021) and the most influential strategy was Strategy 1. Their implementations also have been consistent with the National Tourism Research Strategy Plan in 2017 – 2021 and the most influential strategy was Strategy 4. Furthermore, the findings of these research projects were in response to the 20-Year National Strategy and the most influential strategy was Strategy 2. These projects also were consistent with Strategy 3 of the 12th National Economic and Social Development Plan (2017-2021). In terms of monitoring and evaluation, the fund support of Tourism and Hospitality Industry Research Projects by the National Research Council of Thailand in coordination with the Thailand Research generated positive achievements in the economic, cultural and environmental dimensions, as well as outstanding research works and a group of young researchers with thither potential to do research. Furthermore, the researchers have driven to generate productivity as two tourism and hospitality industry research projects with higher potential towards commercial benefits in the year 2017. These research projects have been used commercially for the WTM 2016 event and as a plan to be presented in WTM 2017 and another one more plan will be commercially used in the national level. Besides, a model for the process of driving the research output in the tourism and hospitality industry has been developed to generate concretely commercial benefits.